Up-regulation of LPS-induced iNOS activity in dibutyryl cyclic AMP-differentiated rat astrocytes. - Song Wei; Zhu Xing-Zu (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of dBcAMP on bacterial endotoxin LPS-induced NOS activity. METHODS: Microscopic changes were observed. Nitrite levels were measured by fluorometric assay. NOS activity was measured by citrulline assay. RESULTS: Within 3-4 h after the addition of dBcAMP 1 mmol.L-1 to culture medium, a morphological transformation reminiscent of in vivo differentiation occurred. Coincubation with LPS and dBcAMP 1 mmol.L-1 resulted in a marked increase in the nitrite production as compared with LPS alone. This increase was concentration- and time-dependent with a maximal effect after 24 h treatment. Nitrite production stimulated by LPS is parallel to the degree of cell differentiation. After a 24-h costimulation with LPS and dBcAMP, L-citrulline formation assay revealed a 3-fold increase in NOS activity over LPS treatment alone. Simultaneous incubation with L-NAME, completely inhibited the stimulation effect of LPS/dBcAMP on nitrite production. Cycloheximide and dactinomycin also suppressed enhancement of NOS activity stimulated by LPS/dBcAMP, both in nitrite production and citrulline assay, indicating that the enhancement of NOS activity was due to the expression of inducible NOS (iNOS) gene and protein. CONCLUSION: Inflammatory signals can trigger astrocytes to express substantially different levels of iNOS depending on their degree of differentiation.